GO Revisited: Qualitative Analysis of the Motivating Factors to Start and Continue Playing GO. Issue 1 (2nd January 2023) - Iizuka, Ai; Yamashita, Mari; Ura, Chiaki; Okamura, Tsuyoshi
ABSTRACT: Purpose: To explore the motivating factors for starting and continuing to play GO among older adults, as well as to examine the effect of GO activities in helping people to live well with, as well as to prevent, dementia. Design: Qualitative descriptive research Methods: Semi-structured interviews were conducted Findings: The participants reportedly started playing GO for dementia prevention, and to cope with their anxieties about aging. They described feeling relaxed while playing GO. They also felt that playing GO fostered human relationships. Conclusions: GO is effective in assisting older adults to cope with aging issues, cultivate peace of mind and encourage interaction with peers. Clinical Evidence: GO is effective in assisting older adults to cope with aging issues, cultivate peace of mind and encourage interaction with peers.